Wednesday
March 29, 2017

Post a New Question

Posted by on .

Solve algebraically and check your potential solutions: sqrt((x+2) -x =0

  • Algebra - ,

    √x+2 - x = 0
    √x+2 = x
    x+2 = x^2
    x^2 - x - 2 = 0
    (x-2)(x+1) = 0

    check for validity

    √(2+2) - 2 = 2-2 = 0 ok
    √(-1+2) - (-1) = 1 - (-1) = 2 nope

    Note that if you had taken the minus √, it would have been ok. But √4 does not mean ±2 - it's just 2.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question